Morality in Communication Between Digital Native Students and Digital Immigrant Lecturers In Higher Education - Nasution, Sumiah; Rosyada, Dede; Puadah, Popi (International Humanity Advance, Business & Sciences, 2025)
This study examines the communication ethics between digital native students and digital immigrant lecturers in higher education. With the rapid advancement of digital technology, communication between these two groups is often influenced by generational differences. The study employs a qualitative research approach, utilizing phenomenology and action research to explore the communication experiences and challenges of both parties. The results indicate that while there are gaps in communication styles and technological adaptation, ethical communication, based on respect, empathy, and understanding, is essential for fostering a positive academic environment. This research also suggests that action research can effectively improve communication practices by promoting awareness of ethical communication standards and bridging generational divides in higher education settings.